2010
DOI: 10.2203/dose-response.09-049.reynolds
|View full text |Cite
|
Sign up to set email alerts
|

Potential Relevance of Bell-Shaped and U-Shaped Dose-Responses for the Therapeutic Targeting of Angiogenesis in Cancer

Abstract: ᮀ Tumor angiogenesis, the growth of new blood vessels into tumors, facilitates tumor growth and thus represents an attractive therapeutic target. Numerous experimental angiogenesis inhibitors have been characterised and subsequently trialled in patients. Some of these agents have failed to show any substantial activity in patients. In contrast, others have been more successful, but even these provide only a few months extra patient survival. Recent work has focused on understanding the effects of anti-angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 138 publications
(180 reference statements)
3
74
0
2
Order By: Relevance
“…Data from pre-clinical and clinical studies in mice and humans showed administration of type 1 IFNs (IFN␣ and -␤) generally exert a linear dose response, whereas exogenous IFN␥ exhibits a "bell-shaped" dose-response curve (83). A "bell-shaped" dose response is characterized by induction of stimulatory effects at low doses until it reaches a summit point where additional dosing cause inhibitory activity and deleterious effects (84). These data suggest the function(s) of endogenous and exogenous IFNs are probably defined by the dynamics between systemic and local inflammatory environments.…”
Section: Ifn-mediated Chronic Inflammation Checkpoint Inhibitors Anmentioning
confidence: 87%
“…Data from pre-clinical and clinical studies in mice and humans showed administration of type 1 IFNs (IFN␣ and -␤) generally exert a linear dose response, whereas exogenous IFN␥ exhibits a "bell-shaped" dose-response curve (83). A "bell-shaped" dose response is characterized by induction of stimulatory effects at low doses until it reaches a summit point where additional dosing cause inhibitory activity and deleterious effects (84). These data suggest the function(s) of endogenous and exogenous IFNs are probably defined by the dynamics between systemic and local inflammatory environments.…”
Section: Ifn-mediated Chronic Inflammation Checkpoint Inhibitors Anmentioning
confidence: 87%
“…A marked increase in microvessel formation at lower doses between 0.625-1.25 µM was also observed. This bell-shaped effect (hormesis) is common in anticancer agents (15,42) which suggests the importance of maintaining the SFN at high concentrations (>5 µM) for cancer chemoprevention or treatment. These tube formation results were consistent with the cell viability data that showed that SFN inhibited the growth of ECs at concentrations of 5-20 µM while at low concentrations of 0.625-2.5 µM, SFN promoted cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…The binding to VEGF receptor is a crucial step in initiation of EC proliferation, migration and differentiation during angiogenesis (13,14). The VEGF signalling system has been suggested as a highly 'druggable' target and potent inhibitors of the VEGF signalling pathway have been used clinically including bevacizumab, sunitinib and sorafeib (15)(16)(17). To date, targeting the HIF/VEGF-VEGFR axis has been a promising strategy for cancer therapy (18).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that sEH inhibition or EETs have biphasic dose-dependent activity on angiogenesis, primary tumor growth, and metastasis. In fact, several angiogenesis modulators, such as α-IFN, endostatin, rosiglitazone, statins, chemotherapy (e.g., 5-fluorouracil, cisplatinum), bortezomib, enterostatin, integrin inhibitors, plasminogen activator-1, rapamycin, thrombospondin-1, TGF-α1, and TGF-α3, have been shown to exhibit a biphasic, U-shaped, or J-shaped dose-efficacy curve known as hormesis (16,17,(30)(31)(32)(33)(34). The sEHIs may be an addition to this growing class of angiogenesis modulators that exhibit a hormesis response.…”
Section: Cox-2/seh Dual Inhibitor Ptupb Inhibits Primary Tumor Growthmentioning
confidence: 99%